2010
DOI: 10.1109/twc.2010.07.060438
|View full text |Cite
|
Sign up to set email alerts
|

Communication in a Poisson Field of Interferers--Part I: Interference Distribution and Error Probability

Abstract: We present a mathematical model for communication subject to both network interference and noise. We introduce a framework where the interferers are scattered according to a spatial Poisson process, and are operating asynchronously in a wireless environment subject to path loss, shadowing, and multipath fading. We consider both cases of slow and fastvarying interferer positions. The paper is comprised of two separate parts. In Part I, we determine the distribution of the aggregate network interference at the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 39 publications
(69 reference statements)
3
115
0
Order By: Relevance
“…The DNS throughput in Nakagami-m fading channels is given by (42), shown at the top of this page, for positive integer m.…”
Section: Theorem 2 (Dns Throughput For Nakagami-m Fading)mentioning
confidence: 99%
See 1 more Smart Citation
“…The DNS throughput in Nakagami-m fading channels is given by (42), shown at the top of this page, for positive integer m.…”
Section: Theorem 2 (Dns Throughput For Nakagami-m Fading)mentioning
confidence: 99%
“…2) Distributed Network Secrecy: The DNS throughput in Nakagami-m fading channels depends on p (l) c , determined by the MAC protocol, according to (42). In particular, we consider an access protocol according to which each legitimate node randomly selects a communication channel independently of other legitimate nodes in the same level [5].…”
Section: A Network Scenario and Performance Analysis 1) Network Scenmentioning
confidence: 99%
“…As in [4], this leads to interference with isotropic α-stable statistics. Applying our recent characterization of the achievable rates of additive isotropic α-stable noise channels in [9], we derive a closed-form expression for the achievable rate of the typical user.…”
Section: Introduction Modern Wireless Communication Network Are Imentioning
confidence: 97%
“…Dynamic interference in wireless networks was introduced in [4,5] by considering a fast-varying (symbol-by-symbol) active transmitter set, with locations governed by a homogeneous Poisson point process. In particular, it was shown that the interfering signal in each time slot is α-stable.…”
Section: Introduction Modern Wireless Communication Network Are Imentioning
confidence: 99%
See 1 more Smart Citation